A practical introduction to beam physics and particle accelerators - Bernal, Santiago (IOP (Series). Release 2., 2016)
This book is a brief exposition of the principles of beam physics and particle accelerators with emphasis on numerical examples employing readily available computer tools. Avoiding detailed derivations, we invite the reader to use general high-end languages such as Mathcad and Matlab, as well as specialized particle accelerator codes (e.g. MAD, WinAgile, Elegant, and others) to explore the principles presented. This approach allows the student to readily identify relevant design parameters and their scaling and easily adapt computer input files to other related situations.